PENENTUAN KOMPOSISI KIMIAWI ATMOSFER DAN TEMPERATUR EFEKTIF PADA BINTANG VEGA (α Lyr) DENGAN MENGGUNAKAN METODE SPEKTROSKOPI ABSORPSI - Fitri Yuliana; Zulkarnain Zulkarnain; Hakim Luthfi Malasan (Universitas Riau, 2019)
The star spectrum is an information which is though to be a map of the star. The shape of the spectral line actually shows the nature of the star atmosphere, which is the only part researcher can be reached. The intensities of spectral lines will determine the chemical composition of the stars contained in the atmospheres of the stars. The approach used to determine the chemical composition and the effective temperature of the star is spectroscopy. The spectroscopy method had been done in this study using the GAO-ITB RTS telescope system which consisting of the Celestron C11 telescope, NEO-R 1000 spectrograph and CCD SBIG ST-8 camera. The object studied is Vega (α Lyr) star which has a magnitude of 0.00 that the main sequence star of the A0 spectrum class. The image data obtained then be processed using IRAF software to obtain the final spectrum graph with the y-axis representing the flux in erg cm-2s-1 and the x-axis representing the wavelength in units of Å. Furthermore, we match the absorption wavelength on the final spectrum graph to the existing wavelength of the Atomic Spectra Database (ASD) to identify the atmospheric chemical composition of the Vega star. Effective temperature can be calculated by using the Wien shifting laws by find out the maximum wavelength of the final spectrum graph. The most found element in the atmosphere of Vega star was hydrogen (H) that consist of Hε, Hδ, Hγ, Hβ, and Hα. The value of effective temperature of the Vega star is 7136 K that has difference percentage of 22.85 % from the mean temperature of A type star.